Glencoe World history: Modern times - Spielvogel, Jackson J. (McGraw-Hill, Glencoe, 2006)
Unit 1. The world before modern times, 3000 B.C.-1800 -- Unit 2. An era of European imperialism, 1800-1914 -- Unit 3. The twentieth century -- Unit 4. Toward a global civilization.